2021
DOI: 10.1016/j.ajogmf.2021.100319
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy as a risk factor for severe coronavirus disease 2019 using standardized clinical criteria

Abstract: more than 11 million people have been infected with coronavirus disease 2019 and almost 250,000 people have died from the disease in the United States, less than 1 year since its discovery. Although literature is beginning to emerge on pregnancy as a risk factor for severe coronavirus disease 2019, these studies are heterogeneous and use primary outcomes such as intensive care unit admission or hospitalization as surrogate markers that may subject analyses to misclassification bias in pregnant patients. OBJECT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
1
7

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 25 publications
1
38
1
7
Order By: Relevance
“…Some subgroups remained reluctant in their willingness to vaccinate; such were female workers aged 20-40, whom many of these were pregnant or considered a pregnancy. It has been well demonstrated that COVID-19 infection in pregnancy is associated with an increased risk of adverse maternal obstetric complications [17], and pregnancy increases the risk of severe COVID-19 disease [18]. On the other hand pregnant people were excluded from the BNT162b2 mRNA Covid-19 vaccine clinical trials, and data regarding the safety of the vaccine in pregnancy at the time of our initial rollout was sparse [19].…”
Section: Discussionmentioning
confidence: 99%
“…Some subgroups remained reluctant in their willingness to vaccinate; such were female workers aged 20-40, whom many of these were pregnant or considered a pregnancy. It has been well demonstrated that COVID-19 infection in pregnancy is associated with an increased risk of adverse maternal obstetric complications [17], and pregnancy increases the risk of severe COVID-19 disease [18]. On the other hand pregnant people were excluded from the BNT162b2 mRNA Covid-19 vaccine clinical trials, and data regarding the safety of the vaccine in pregnancy at the time of our initial rollout was sparse [19].…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the pregnancy outcomes of the patients with severe symptoms 3 due to the altered immune system during pregnancy. [10] In this study, we investigated symptomatic pregnant women who had mild-moderate and severe COVID-19 infection during pregnancy. We found gestational age at diagnosis of COVID-19 was higher in the severe patient group than the mild-moderate group (p=0.048) and there was no difference regarding pregnancy and neonatal outcomes between the severe and non-severe groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several biological studies have identified sex and age differences in biological pathways related to SARS-CoV-2 infection and support our findings. [20][21][22] Pregnancy has been previously identified as a potential risk factor for ICU admission 23,24 and severe disease, 25 but most studies have been limited to pregnant women who were already hospitalized (including for non-COVID-19 reasons such as childbirth). 23,26 This finding could be in part the result of a lower clinical threshold for hospitalization of pregnant patients.…”
Section: Discussionmentioning
confidence: 99%